Pemikiran Taha Husain - Annur, Barsihannor (Al-Hikmah Journal for Religious Studies, 2014)
Taha Husain was an intellectuals figure who was very controversial with his ideas. He disclosed some reform idea that was considered âstrangeâ and irrasional. Â According to him,Â  Â toÂ  Â advanceÂ Â  theÂ  Â moslemÂ  Â world,Â  Â secularizingÂ  Â the education and religion must be implemented. The old Egypt and modern West must become role model how to develop moslem world. Religion could not be mixed with politic. religionÂ  Â mustÂ  Â beÂ Â  separatedÂ  Â fromÂ  Â politic.Â  Â ToÂ  Â beÂ Â  the enlightened nation, the people who live in the country must be educated with standardized education. According to Taha Husain, Western education was a good model of education which can be implemented.